Controlling cracks in reinforced concrete beam using polymer modified mortar by different method - Wan Syariah, Wan Jamaluddin (2014)
The most common defect in concrete structures is the cracks. Cracking in concrete will affect the appearance, workability and the strength of the concrete structures. It may indicate the occurrence distress of the structure or less of durability, thus it will make not safe for application. The structure that damaged must be repaired to bring back its structure strength. This research investigates the efficiency of polymer modified mortar as a material for repair cracks. For this study of controlling crack, three beams of grade 20 strength were casted and repaired by three different methods. All the beam samples were tested by one point load test until first crack appear. The repair methods covered for this study were using polymer modified mortar by injection, patching and underlay coating. The beams were tested for second time until failure to get the deflection, ultimate load and pattern of cracks. Between this three methods of repairing cracks in beam using polymer modified mortar, underlay coat method showed the less differences of load and deflection between repaired and initial beam which were 83.1% and 26.8% respectively. Patch method resulted the least of 69.9% of load and 3.4% of deflection differences while inject method indicated 78% and 8.6% of differences in load and deflection respectively between initial and repaired beam. Most of cracks happened at the same places after they were repaired in flexural and shear patterns. For this study, less of polymer modified mortar was used for remove cracks due to less than 1 mm width of cracks. However, in real situation of the structures are remaining under condition of permanent forces, polymer modified mortar will apply more into cracks for the good results.